2021
DOI: 10.3389/fphar.2021.578716
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Effectively Attenuates Olanzapine-Induced Body Weight Gain in Female Wistar Rats

Abstract: Atypical antipsychotic drugs are commonly associated with undesirable side effects including body weight gain (BWG) and metabolic deficits. Many pharmacological interventions have been tested in an attempt to minimize or prevent these side effects. Preliminary evidence suggests that antidiabetic drugs may be effective in attenuating antipsychotic-induced BWG. In the current study, we examined the effect of an antidiabetic drug empagliflozin (EMPA) on BWG induced by anatypical antipsychotic drug olanzapine (Ola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…In the reported preclinical study, researchers evaluated the effects of empagliflozin on body weight gain induced by olanzapine administration in female and male Wistar rats (31). Olanzapine induced a sustained increase in body weight in this population, while the subsequent treatment with empagliflozin attenuated the antipsychotic-induced weight gain only in female rats (31). Clinical guidelines and expert consensus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the reported preclinical study, researchers evaluated the effects of empagliflozin on body weight gain induced by olanzapine administration in female and male Wistar rats (31). Olanzapine induced a sustained increase in body weight in this population, while the subsequent treatment with empagliflozin attenuated the antipsychotic-induced weight gain only in female rats (31). Clinical guidelines and expert consensus.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the current literature review, it can be concluded that SGLT2Is may be added to metformin in selected cases of type 2 diabetes mellitus in the context of antipsychotic treatment, as suggested by a clinical guideline and an expert consensus; a case report and a systematic review also support this strategy ( 1 , 32 , 33 , 37 ). Evidence to support the administration of SGLT2Is as second-line treatment in patients with diabetes mellitus who are also treated with olanzapine or clozapine is derived from very limited preclinical ( 31 ) and clinical data ( 37 ). The advantages of SGLTI2s, i.e., the low risk of hypoglycaemia and the associated weight loss properties, may recommend these agents, along with GLP-1RAs and DPP-4Is, as preferred options for second-line therapy in patients with severe mental disorders ( 33 ).…”
Section: Conclusion and Clinical Observationsmentioning
confidence: 99%
“… 61 Norepinephrine, epinephrine and catecholamine are hormones that are very important in the regulation of many metabolic processes. These hormones have been shown to play an essential role in the metabolic side effects of antipsychotics, both in human and animal studies, 62 , 63 which revealed a dose-dependent increase in rodent models. 64 The strong affinity of antipsychotics for 5-HT2C and H1 receptors is considered the primary cause of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…The body weight of the rats was monitored on a regular and daily basis. It was measured in grams (g), with a Scaltec SBA 52 balance, and the growth rate of the rats from day one was expressed as a percentage and calculated according to the following formula [97]:…”
Section: Monitoring Of Rat Body Weightmentioning
confidence: 99%